PROMOTION OF CASSAVA CHIPS &Quot;TETTE&Quot; THROUGH INSTAGRAM AND FACEBOOK ACCOUNTS AT BUMDES MADULANG, OMBEN DISTRICT, SAMPANG REGENCY - Fedianty AUGUSTINAH (Pusat Pengabdian kepada Masyarakat- LPPM Universitas Terbuka, 2019)
Partners in the Community Partnership Program are Madulang Village-Owned Enterprises (Bumdes) in Omben District, Sampang Regency, which is managed by the Head of Madulang Village who has managed the production of Cassava Chips known as Tette. Madum Bumdes Kripik Cassava TETTE so far only uses one of the social media namely Whattshap (WA) alone as a means of promotion to sell its products but Madum Bumdes still has not utilized the various applications that have been provided by social media either through Android Mobile or wifi facilities that are currently rife at regions / villages at this time so that it can be said that the use of promotional facilities has not been maximized using Social Media such as Instagram and Facebook which has a wider range of promotions to increase the sales volume of TETTE chips. Some things that are considered a priority issue by Bumdes Madulang partners are problems creating accounts through social media Instagram and Facebook and marketing TETTE cassava chips through social media Instagram and Facebook. The solution provided is in the form of training (coaching and mentoring) carried out with the first chronological or phased strategy that is giving knowledge / opening insights to Madulang Village Business Entrepreneurs about the importance of using Facebook and Instagram social media as a means of promoting TETTE cassava chips and the second provide training on making Facebook and Instagram accounts as a means of promoting TETTE cassava chips. The third solution activity was to produce photos and promotional videos of TETTE sigkong chips. to fill Facebook and Instagram accounts and the fourth agreed solution is to evaluate the promotion of TETTE sigkong chips that have been carried out by Madulang Village-Owned Enterprises through social media accounts Facebook and Instagram. Suggestions that can be used by several related parties to assist in the development of the business of tette chips in Bumdes Madulang, District of Omben, Sampang Regency, training for the use of social media as a means of promotion at present where training related to marketing and marketing communication through